Effects of concurrent perioperative use of marbofloxacin and cimicoxib or carprofen in dogs. (31st March 2016) - Weil, C.; Tünsmeyer, J.; Tipold, A.; Hoppe, S.; Beyerbach, M.; Pankow, W.‐R.; Kästner, S. B.
Abstract : Objectives : To investigate possible interactions visible on electroencephalogram recordings caused by concomitant administration of marbofloxacin and carprofen or cimicoxib in dogs without central nervous system disease. Methods : Totally 21 client‐owned dogs undergoing different surgeries were included in a randomised, blinded, clinical study. Each dog was assigned to one of two groups treated with either carprofen or cimicoxib pre‐ and postoperatively. After anaesthetic induction both groups received marbofloxacin intravenously while recording an electroencephalogram. Offline electroencephalogram analysis included qualitative evaluation and Fast Fourier Transformation. Postoperative analgesia was evaluated for 24 hours and after 10 days with the short‐form Glasgow Composite Measure Pain Scale. Statistical analysis included Wilcoxon signed rank test, Mann–Whitney U test and Student's t ‐test with α set at 5%. Results : Marbofloxacin injection caused no effects on quantitative and qualitative electroencephalogram parameters in both groups. No differences in postoperative pain scoring were found between treatment groups. Clinical Significance : Concurrent use of marbofloxacin with either cimicoxib or carprofen did not induce neuroexcitatory activities in dogs without CNS disease directly after administration.